Securing Office 365 Masterminding MDM and Compliance in the Cloud - Katzer, Matthew (Apress, 2018)
Understand common security pitfalls and discover weak points in your organization's data security, and what you can do to combat them. This book includes the best approaches to managing mobile devices both on your local network and outside the office. Data breaches, compliance fines, and distribution of personally identifiable information (PII) without encryption or safeguards place businesses of all types at risk. In today's electronic world, you must have a secure digital footprint that is based on business processes that are designed to protect information. This book is written for business owners, chief information security officers (CISO), and IT managers who want to securely configure Office 365. You will follow the Microsoft cybersecurity road map through a progressive tutorial on how to configure the security services in Office 365 to protect and manage your business. What You'll Learn: Manage security with the Azure Security Center and the Office 365 Compliance Center Configure information protection for document and electronic communications Monitor security for your business in the cloud Understand Mobile Application Management (MAM) and Mobile Device Management (MDM) Prevent data loss in Office 365 Configure and manage the compliance manager tools for NIST and GDPR This book is for IT managers and compliance and cybersecurity officers who have responsibility for compliance and data security in their business. Matthew Katzer created KAMIND in 1998 to supply solutions using Microsoft and Intel Technologies for small- and medium-sized businesses. Prior to creating KAMIND, Matt worked for Intel Corporation for 17 years managing engineering development, IT projects, and working with the Intel security group. After leaving Intel, Matt pursued the development of technology-related inventions and holds 19 domestic and international patents in related areas. Matt's focus with cloud solutions started in 2009, looking at ways for businesses to improve productivity and manage and secure digital business assets. Matt holds a BSEE degree from the University of Michigan and an Executive MBA from the University of Oregon.